Evolution of Doric Frieze Forms. Methods of Geometric Morphometrics in Statistical Analysis of Architectural Elements - Kolosov, Vladimir P. (Actual Problems of Theory and History of Art, 2015)
Method of geometric morphometrics and multivariate statistics applied to differentiate forms and shapes of architectural elements is presented in the paper. Preliminary systematization of architectural fragments was used. As an example, a sample of 83 elements of Doric triglyph-metope frieze, well known architectural monuments and new archaeological finds among these, was taken for the statistical analysis. Architectural details under research originate from different regions of the Ancient World. Chronological frameworks cover long period from Archaic time to early centuries AD. Finally, as a result of the work, patterns of geometrical variability of triglyphs that testify the existence of several rather invariable forms were distinguished. Five variants of triglyph configuration are identified and confirmed by regional and chronological features.